Unidimensionality of the personality inventory for DSM-5 facets: Evidence from two Czech-speaking samples - Riegel, Karel D; Ksinan, Albert J; Samankova, Dita; Preiss, Marek; Harsa, Pavel; Krueger, Robert F (Personality and mental health, 2018)
To date, numerous studies have confirmed empirical relevance of the personality trait model defined in the Alternative DSM-5 Model for Personality Disorders. The supposed single-factor structure of its facets and general domains across various samples, however, has not been researched thoroughly. This study focused on evaluating the hypothesized unidimensional factor structure of the lower-order personality trait facets, as well as the validity of the higher-order domains. The Czech version of the Personality Inventory for DSM-5 (PID-5) was used in a sample of 351 community volunteers and 143 psychiatric patients. The fit of the model for 25 facets could not be replicated with the original PID-5, while a shortened version confirmed the single-factor structure of all facets and their relevance to the five proposed domains. The findings support unidimensional structure of the modified DSM-5 personality trait model and imply discussion of the utility of the proposed PID-5 version. Copyright © 2018 John Wiley & Sons, Ltd.
Keywords: Personality Disorders; Humans; lidé středního věku; Models, Psychological; Personality Inventory; poruchy osobnosti; osobnostní dotazník; Female; Aged; mladý dospělý; dospělí; faktorová analýza statistická; senioři; lidé; Factor Analysis, Statistical; Adult; ženské pohlaví; Male; Middle Aged; Adolescent; Psychometrics; psychologické modely; Diagnostic and Statistical Manual of Mental Disorders; Czech Republic; Diagnostický a statistický manuál mentálních poruch; osobnost; Young Adult; Personality; Česká republika; mužské pohlaví; psychometrie; mladiství